Characterization of mainstream cigarette smoke aerosol by size-fractionated chemical analysis of nicotine, solanesol, and tobacco-specific nitrosamines. (3rd July 2020) - Cui, Huapeng; Yurteri, Caner U.; Cabot, Ross; Xie, Fuwei; Liu, Huimin
Abstract: The distribution of key chemicals in mainstream cigarette smoke (MCS) particles of different sizes have implications for respiratory dose. In this study, a differential mobility spectrometer (DMS) and an electrical low-pressure impactor (ELPI) were used to characterize MCS particles generated from three cigarettes (3R4F, Dunhill, and Hongtashan). In addition, the ELPI was used to collect smoke particles of three different aerodynamic diameters (144, 431, and 722 nm) from 3R4F MCS, which were analyzed for nicotine, solanesol and tobacco-specific nitrosamines (TSNAs). The number concentration, particle size distribution, and count median diameter (CMD) of the MCS particles characterized by DMS and ELPI were compared quantitatively. The observed difference in the physical characterization results of MCS particles may be due to a myriad of discrepancies between the two techniques. Chemical analyses of the three ELPI selected particle sizes showed that, after normalization to total particulate matter (TPM), nicotine and TSNAs were distributed evenly, whereas solanesol showed a tendency to increase with increasing particle diameter. Notably, the distribution of nicotine and four TSNAs was independent of the three particle sizes; however, the amount of solanesol showed a slight dependency on particle size, varying by less than 23.4% over the size range considered.